Animation socioculturelle enfance et jeunesse Résultats de la première enquête nationale suisse - Gerodetti, Julia (Seismo, 2021)
This book presents an overview of the results of the first standardised survey of services of open child and youth work in Switzerland, which was conducted in 2018 as a sub-project of the project Language Regions of the umbrella organisation Open Child and Youth Work Switzerland (DOJ/AFAJ) and other cooperation partners and was published in the three national languages of Switzerland which are German, French and Italian. A total of 620 services of open child and youth work, in which at least one permanently employed and/or paid professional worked, took part in the survey. In the book, the following aspects of the field of action are described in an overview and then contextualised: Types of services, opportunities for participation, quality work, professional orientation, financing, sponsorship and governance and management structures, statements on the target group, clients and staff, as well as on spatial or financial resources, founding year, opening hours etc., but also assessments of the professionals on specific topics. The results were also compared between the different linguistic regions and in the three different types of communes "urban", "intermediate" and "rural". The results of the study show a picture of a differentiated and complex field of action, illustrate achievements to date and point out the potential for future development.